Development of the salto in men's floor exercise: - Morii, R.; Watanabe, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The exercise elements included in the sport of artistic gymnastics never remain constant, and continue to transform with the times. For an adequate understanding of today`s exercise elements and techniques, it is essential to recognize the historical and sociocultural premises that have affected their evolution. However, research on the historical development of gymnastic techniques has received little attention over the last 40 years. As a result, we are facing a situation where the historical link between exercise elements and the background factors affecting their evolution has become poorly defined. The present research focused on the evolution of the salto in the men`s floor exercise during the 1970s to 1980s, in order to achieve a basic understanding of today`s exercise elements and techniques, and to anticipate future developments by studying the factors determining the development of the exercise elements in accordance with the changes made to the code of points and apparatuses. This study clarified the following points. 1. It was possible to systematically organize the history of salto development, which had hitherto remained unclear. 2. From the 1970s to 1980s, notable developments primarily in the double backward salto were seen, and it became clear that these developments had been significantly impacted by the effects of awarding "bonus points for risk and originality", together with improvements in the elasticity of the gymnastics floor. 3. Accordingly, it became clear that changes to the "techniques of exercise elements" such as cross-techniques for the double backward salto and the acceleration speed from round off to the back handspring were also affected by the above factors. 4. It became clear that a problem was emerging with the systematic positioning of the backward jump with the 3/2 salto tucked and 3/2 twist, an element developed from the forward salto using the "twist" technique. This research will aid the proper evaluation of today`s floor exercise elements and techniques and the retention of exercise elements and techniques that will be developed in the future, serving as a guideline for efficient coaching at actual training sites.